Graphene oxide-based optical waveguide for moisture sensing in transformer oil - Karthikeyan, S.; Mezher, Mezher H.; Ibrahim, Fatimah; Vigneswaran, Dhasarathan; Amiri, Iraj Sadegh; Zakaria, Rozalina (Elsevier, 2019)
We report on moisture detection in transformer oil based on an optical waveguide fabricated using graphene oxide (GO). The SU-8 polymer channel waveguide was coated by GO film, using a drop-casting technique. Here, for the polarized light, high absorption of transverse electric (TE) was achieved for the proposed sensor at wavelength 1550 nm. Changes in TE-polarized light absorption by the device were measured at varying water contents. Experiments were carried out for water contents in oil in the range of 16–21 ppm as well as immiscible (free) water in oil. Our observations showed a difference in the results trend obtained for different relative water contents. The TE-transmission power increased linearly with higher water content in transformer oil. A power change of +0.90 dB/ppm of water content in transformer oil was measured within the range tested. A simulation analysis using the finite element method FEM was also carried out. The proposed sensing mechanism can be used under these sensing conditions. This approach also has a fast response time as well as high sensitivity. © 2019 Elsevier B.V.